Time Course Analysis of Transcriptome in Human Myometrium Depending on Labor Duration and Correlating With Postpartum Blood Loss - Chen, Lina; Luo, Yihong; Chen, Yunshan; Wang, Lele; Wang, Xiaodi; Zhang, Guozheng; Ji, Kaiyuan; Liu, Huishu (Frontiers in Genetics, 2022)
he maintenance of coordinated powerful episodic contractions of the uterus is the crucial factor for normal labor. The uterine contractility is gradually enhanced with the progression of labor, which is related to the gene expression of myometrium. Competing endogenous RNA (ceRNA) can also regulate the gene expression. To better understand the role of ceRNA network in labor, transcriptome sequencing was performed on the myometrium of 17 parturients at different labor durations (0-24 h). From this, expression levels of mRNA, long non-coding RNA (lncRNA), circular RNA (circRNA) and microRNA (miRNA) were correlated to labour duration. Then, targeting relationships between mRNAs, lncRNAs, circRNAs and miRNAs were predicted, and the ceRNA regulatory network was established. The mRNA expression patterns associated with cervical dilation and postpartum bleeding were further investigated. This analysis identified 932 RNAs positively correlated with labor duration (859 mRNAs, 28 lncRNAs, 45 circRNAs) and 153 RNAs negatively correlated with labor duration (122 mRNAs, 28 lncRNAs, and 3 miRNAs). These mRNAs were involved in protein metabolism, transport and cytoskeleton functions. According to the targeting relationship among these ceRNAs and mRNAs, a ceRNA network consisting of 3 miRNAs, 72mRNA, 2 circRNAs and 1 lncRNA was established. In addition, two mRNA expression patterns were established by time-series analysis of mRNA expression in different phases of cervical dilation. A ceRNA network analysis for blood loss was performed, postpartum bleeding was closely related to inflammatory response, angiogenesis and hemostasis. This study identified human myometrial transcriptome and established the ceRNA regulatory network depending on labor duration, highlighted the dynamic changes that occur at ceRNAs during parturition, which need to be considered more in future to better understand how changes in gene expression are relevant to functional changes in human myometrium at labor.